Antwoord:
Zie onder.
Uitleg:
Laat # 1 + costheta + isintheta = r (cosalpha isinalpha +) #, hier # R = sqrt ((1 + costheta) ^ 2 + sin ^ 2 theta) = sqrt (2 + 2costheta) #
= #sqrt (2 + 4cos ^ 2 (theta / 2) -2) = 2cos (theta / 2) #
en # Tanalpha = sintheta / (1 + costheta) == (2sin (theta / 2) cos (theta / 2)) / (^ 2 2cos (theta / 2)) = tan (theta / 2) # of # Alpha theta / 2 #
dan # 1 + costheta-isintheta = r (cos (alfa) + isin (alfa)) = r (cosalpha-isinalpha) #
en we kunnen schrijven # (1 + costheta + isintheta) ^ n + (1 + costheta-isintheta) ^ n # de stelling van DE MOivre gebruiken als
# R ^ n (cosnalpha isinnalpha + + cosnalpha-isinnalpha) #
= # 2r ^ ncosnalpha #
= # 2 * 2 ^ n ^ ncos (theta / 2) cos ((ntheta) / 2) #
= # 2 ^ (n + 1) cos ^ n (theta / 2) cos ((ntheta) / 2) #